1989
DOI: 10.1063/1.455801
|View full text |Cite
|
Sign up to set email alerts
|

The electronic spectrum of NOCl: Photofragment spectroscopy, vector correlations, and a bi n i t i o calculations

Abstract: The electronic absorption spectrum of NOCl in the region 620–180 nm is assigned by using vector properties of the NO photofragment and the results of ab initio calculations at the CI level. In assigning the electronic spectrum, we take into account the recoil anisotropy, rotational alignment, and Λ-doublet populations of NO, as well as the calculated vertical excitation energies, oscillator strengths, and the nature of the orbitals involved in the transitions. In the experiments, we use expansion-cooled sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
78
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 22 publications
9
78
0
Order By: Relevance
“…As mentioned in the Introduction, photochemical studies of gaseous ClNO employing wavelengths resonant with the A-band have shown that Cl and NO formation is the dominant photochemical pathway. 25,36,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] In contrast, the structural isomer (ClON) is the only photoproduct observed in low-temperature matrix studies. 63,64 The results presented here represent the first detailed measurements of ClNO photochemistry in solution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned in the Introduction, photochemical studies of gaseous ClNO employing wavelengths resonant with the A-band have shown that Cl and NO formation is the dominant photochemical pathway. 25,36,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] In contrast, the structural isomer (ClON) is the only photoproduct observed in low-temperature matrix studies. 63,64 The results presented here represent the first detailed measurements of ClNO photochemistry in solution.…”
Section: Discussionmentioning
confidence: 99%
“…38 The photochemistry of gaseous ClNO is dominated by formation of the photoproducts, NO ( 2 Π ( 1 / 2 , ( 3 / 2 ) and Cl ( 2 P 1/2,3/2 ), with near-unity quantum yield. 25,36,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] The absorption spectrum of ClNO consists of a series of bands referred to as the K through A bands as one proceeds from low to high energy. 57,58 The A-band dominates the absorption spectrum and has an absorption maximum of 196 nm in the gas phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ClNO has a low bond dissociation energy (13 000 cm-l) (29) and absorbs light throughout the visible and ultraviolet -spectral regions that are easily accessed with tunable dye lasers. The 300 K absorption spectrum consists of several broad absorption bands (32), which have recently been assigned (30). Its NO product state distributions, photofragment yield spectra, recoil anisotropy, rotational alignment, NO A-doublet populations and the nature of the orbitals involved in electronic transitions have been determined both experimentally and theoretically (28-3 1).…”
Section: Introductionmentioning
confidence: 99%
“…At 355 nm, gas phase ClNO is excited via a parallel transition, s3(21Ar) t sO(llA'), yielding rotationally hot NO, i.e., = 46.5 (29,30). Almost all of the NO is in v" = 0.…”
Section: Introductionmentioning
confidence: 99%